Perbandingan Kapasitas Kolom Beton Bertulang Berdasarkan Variasi Bentuk Sengkang dengan Analisis Finite Element Method - Anam, M.K.; Amir, F.; Sutrisno, M. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
Columns are one of the structural elements that greatly influence the behaviour of the structure. Columns are capable of holding axial compression loads and transmitting them to the structural elements below. Column capacity can be increased by the confinement of lateral reinforcement/stirrup. The stirrups function to maintain the compressive strength capacity of the concrete column before and after spalling. Advances in software technology have had a very significant impact on the development of structural element analysis methods, including software based on the Finite Element Method (FEM), Abaqus/CAE Student Edition. It can also simplify several laboratory research of Civil Engineering into a simulation. However, in simulation practice, parameters in the form of material data are needed as input. To get the same behaviour between the test object and the simulation, convergent parameters are needed. The parameters to be analyzed are CDP (Concrete Damage Plasticity) plastic parameters. While the simulation for loading, shape of the test object, and placement refers to the results of previous studies. The reinforced concrete column test model used consists of 5 (five) different variations of stirrups. The results of the simulation show that reinforced concrete columns with stirrups provide support in the form of shear force capacity that can maintain the value of the axial compressive strength capacity. From the five existing test models, it was obtained that the increase in the value of the axial compressive strength capacity of the column due to the variation of stirrups for column B, column C, column D, and column E to column A (without stirrups) were 115%, 120%, 121%, and 119% consecutively. The output values from the analysis include the diagrams of axial force and displacement, column interaction diagrams, and material stress-strain diagrams